Hubungan Kontrol Diri dengan Perilaku Hedonisme Mahasiswa dalam Menggunakan Marketplace - Rahmadani, Putri; Yendi, Frischa Meivilona; Sukma, Dina; Putriani, Lisa; Handayani, Puji Gusri (Universitas Negeri Padang, 2024)
A phenomenon that is currently occurring among teenagers, especially students, is hedonism behavior. One factor that can influence hedonism behavior is self-control. The lack of self-control possessed by students is the cause of hedonism behavior. The aim of this research is to determine the relationship between self-control and students' hedonism behavior in using the marketplace. This research is a type of descriptive and correlational quantitative research. The results of this study show that (1) self-control is in the medium category (57.34%), (2) hedonism behavior is in the medium category (84.17%), (3) The results of the correlation analysis show a negative and significant relationship between self-control (X) with hedonism behavior (Y) with a calculated r value of -0.954 with a significance level of <0.001 at a medium relationship level. Based on the research results, guidance and counseling teachers/counselors can provide assistance to prevent and overcome hedonism behavior by providing information services, individual counseling services and group guidance services.